Identifying Different Halogen‐/Hydrogen‐Bonding Interaction Modes in Binary Systems that Contain an Acetate Ionic Liquid and Various Halobenzenes. Issue 9 (17th April 2018) - Xu, Jing; Zhou, Yu; Deng, Geng; Ashraf, Hamad; Yu, Zhi‐Wu
Abstract: The front cover artwork is provided by the group of Prof. Zhi‐Wu Yu at Tsinghua University. The image shows two different interaction modes between two halobenzenes and an acetate‐based ionic liquid (IL). The IL is a potentially good solvent to halogenated drug molecules. Read the full text of the Article at 10.1002/cphc.201701302 . Abstract : "The nature of noncovalent interactions between ionic liquids and halogenated molecules is of particular importance for both fundamental research and drug development. Herein, the noncovalent interactions between 1‐butyl‐3‐methyl‐imidazolium acetate and three halobenzenes C6 F5 X (X=I, Br, H) were investigated…" This and more about the story behind the front cover can be found in the Article at10.1002/cphc.201701302 .